From the user's perspective: Perceptions of risk relative to benefit associated with using the Internet. (June 2016) - Byrne, Zinta S.; Dvorak, Kyla J.; Peters, Janet M.; Ray, Indrajit; Howe, Adele; Sanchez, Diana
Abstract: We departed from existing studies on Internet use by exploring users' perception of their own use of the Internet. Using a mixed-method explanatory sequential design approach, we first asked users to generate lists of actions they take on the Internet and then asked them why they engage in these 35 activities. Using the information gleaned from the interviews, we developed surveys that asked 261 users (ages 19–68) to rate the perceived risk (defined as situations that contain uncertainty regarding outcomes and/or possess the potential for negative consequences) associated with each action, benefits received from each action, frequency with which they engage in the action, and amount of information they are willing to share to engage in the action. We also assessed a number of individual difference characteristics. Our study results (1) provide an Internet Action list usable in future studies; (2) provide an initial understanding that users (to a degree) engage in Internet actions for the benefits they perceive they gain; (3) show that users share little personal information, if any, to get those benefits; and (4) users have little ability to accurately evaluate the true risk (i.e., due to Internet threats) associated with those actions. Highlights: Users generated 35 Internet actions they say they take on the Internet. Users provided frequency ratings, risk perceptions, and benefits for each action. We compared user rated risk perceptions to expert ratings of risk for each action. Tendency towards risky behavior was unrelated to risk and frequency ratings. Younger and older adult users rate risks and gains about the same.